Daily night-time lights reveal prolonging global electric power system recovery times following tropical cyclone damage - Yu Mo; Fred Thomas; Jianan Rui; Jim W Hall (Environmental Research: Infrastructure and Sustainability, 2025)
Tropical cyclones are a leading cause of electric power outages, and the time required for power system recovery after storm damage is a critical measure of system resilience. However, systematically collected data on power supply disruptions are available for only a limited number of countries, leaving global patterns largely unexplored. In this study, we conducted the first global analysis of electric power system recovery times after 396 storms across 66 countries from 2012 to 2021, using satellite-based daily nighttime lights (NTLs) derived blackouts following storms. The median duration of blackouts detected worldwide was 4 d, with 5th–95th percentiles of 1–12 d. We found that high density urban areas had significant ( P < 0.05) longer blackout events than low density urban areas and rural areas, which was driven by the upper tail of the events (i.e. 95 percentiles of, respectively, 16, 12, and 11 d). We also found that blackout durations have significantly ( P < 0.05) increased over the study period across all levels of urbanization, at a similar rate of 0.9 ± 0.1 d per decade. The temporal variations (i.e. annual means) of blackout duration of high and low density urban clusters negatively correlated with storm travel speed, while those of low density urban clusters and rural areas positively correlated with pre-storm NTL ( P ⩽ 0.05 in all cases). These findings highlight the pressing need to strengthen the resilience of electric power systems to storms, particularly as global reliance on electricity grows and storm activity patterns shift in response to climate change.